(untitled) (Global Journal of Human-Social Science, 2020)
Artists in Ghana who produce sculptural busts or portraits mostly limit their production materials to clay, P.O.P., cement, and metal cast. These materials may have defects and could be potentially affected by environmental conditions for lifelong periods. Aluminium welding is not practiced by artists in the fabrication of photorealistic portraits. The techniques used by artists in Ghana is the clay and cement model, which can further be used in the creation of a cast resin or metal. The researchers investigated the most used materials for creating realistic busts. The pros and cons of the materials as well as their techniques were rigorously analyzed in comparison with the aluminium forming and welding technique. Welders are constrained as far as what they can create. Mostly welders produce iron gates, burglar-proof and security locks. There is the need to diversify the technique to be able to produce portraits as a step in experimenting and diversifying the material and technique.